Leadership in the crucible : the Korean War battles of Twin Tunnels & Chipyong-ni - Hamburger, Kenneth Earl, 1941- (College Station : Texas A & M University Press, 2003)
Annotation At the pivotal battles of Twin Tunnels and Chipyong-ni in February 1951, U.N. forces met and contained large-scale attacks by Chinese forces. Col. Paul Freeman and the larger-than-life Col. Ralph Monclar led the American 23rd Infantry Regiment and the French Bataillon de Coree, respectively. In this careful consideration of combat leadership at all levels, Kenneth E. Hamburger details the actions of these units, offering stories of men sustaining themselves and one another to the limits of human endurance. He analyzes the roles that training, cohesion, morale, logistics, and leadership play in success or failure on the front lines, providing a well-organized discussion that is sure to become a classic in the field of leadership studies. Lt. Gen. Matthew Ridgway, Eighth Army commander, and Lt. Col. Ralph Monclar, the French Battalion commander, March 1951.
The 23d infantry regiment and col. Paul Freeman -- Baptism by fire on the Naktong River line -- Disaster in the north -- The French battalion and lt. col. Ralph Monclar -- Matthew Ridgway and a new war -- Wonju and patrols to Twin Tunnels -- The battle of Twin Tunnels -- Prelude to Chipyong-ni -- Isolated and encircled at Chipyong-ni -- Fighting and surviving on the second day -- Task force Crombez runs the Gauntlet -- Aftermath and reflections.
Includes bibliographical references (pages 231-249) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: United States. -- Army. -- Infantry Regiment, 23rd (1866-1957) -- History -- 20th century; France. -- Armée. -- Bataillon de Corée -- History; France. -- Armée. -- Bataillon de Corée; United States. -- Army. -- Infantry Regiment, 23rd (1866-1957); Chipyong-ni, Battle of, Chipʻyŏng-ni, Korea, 1951.; Twin Tunnels, Battle of, Korea, 1951.; Korean War, 1950-1953 -- Regimental histories -- United States; Korean War, 1950-1953 -- Regimental histories -- France; Guerre de Corée, 1950-1953 -- Histoire des unités -- États-Unis.; Guerre de Corée, 1950-1953 -- Histoire des unités -- France; HISTORY -- Military -- Korean War; Regimental histories; France; Korea; Korea (South) -- Chipʻyŏng-ni; United States; 1900-1999; History